Penerapan Metode Data Mining Market Basket Analysis Terhadap Data Penjualan Produk Pada Toko Tas Branded Menggunakan Algoritma Apriori - Wulan Dari; Dian Maya Sari; Nurul Nazli (Universitas Katolik Widya Karya Malang, 2023)
Data mining is a technique to extract new information from the data warehouse, information is considered very important and valuable because by mastering the information so easily to achieve a goal, this makes everyone competing to obtain information, as well as on trading businesses such as bag store BRANDED. store is located close to the home of the population, this certainly affects the level of sales, with the daily sales activities, sales transaction data will continue to grow, causing data storage is greater. Sales transaction data is only used as an archive without being put to good use. Basically the data set has very useful information. The analysis of market basket with Apriori Algorithm is one method of data mining which aims to find the pattern of association based on consumer spending pattern, so that it can be known what items are purchased simultaneously. The result of this research found that the highest support and confidence value is Ysl and Chanel with a support value of 50% and confidence of 75%.